Paraguay : 2010 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Paraguay. (IMF Staff Country Reports; Country Report ;, 2010)
This Article IV Consultation reports that the overall balance of the central government of Paraguay is expected to be in equilibrium, while the central bank intends to withdraw excess liquidity as necessary to limit inflation to no more than 5 percent. Executive Directors commended the Paraguayan authorities for preserving macroeconomic stability in 2009 in the face of a severe drought and the global financial crisis. They emphasized the importance of fiscal reforms, aimed at increasing the tax ratio, strengthening fiscal management, and reducing fiscal risks.